Correction of bifid nose with tongue-in-groove technique in patient with Tessier fissure 0-14 - De Menezes Neto, Balduino Ferreira; Secanho, Murilo Sgarbi; Carvalho, Laisa Brandão; Moragas, Weber Ribolli; Costa, Paulo Victor Cunha; Palhares, Aristides Augusto (Thieme, 2022)
Introduction: Craniofacial anomalies are usually identified by their appearance. Over time, several scales and classifications were proposed based on clinical and anatomical aspects. In 1976, Tessier made an association between soft tissue and underlying bone. With this concept, he created a numeral system starting from the clockwise orbit of 0-which he called the zero line, a vertical line of the face-to 14. Rare and with multiple presentations, its conduction is a challenge even for more experienced professionals. Case Report: Female patient who underwent open structured rhinoplasty at the age of 15 to correct a bifid nose, using costal cartilage and the tongue-in-groove technique. Discussion: Bifid nose is one of the main presentations of cleft 0. Structured open rhinoplasty has already been successfully applied in other studies, and the tongue-in-groove technique is especially useful for the projection and rotation of the nasal tip. Conclusion: Craniofacial anomalies vary in their presentations, and it is up to the plastic surgeon to identify the problems and propose therapeutic solutions that alleviate these changes. Their treatment will require a thorough preoperative assessment, careful surgical planning, and meticulous surgical technique.
Correção de nariz bífido com técnica tongue-in-groove em paciente com fissura 0-14 de Tessier
Keywords: Congenital abnormalities; Costal cartilage; Craniofacial abnormalities; Nose; Rhinoplasty